2023
DOI: 10.3390/pathogens12020161
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of Indoor Air Fungal or Chemical Toxins with Caenorhabditis elegans nematodes

Abstract: Bad indoor air quality due to toxins and other impurities can have a negative impact on human well-being, working capacity and health. Therefore, reliable methods to monitor the health risks associated with exposure to hazardous indoor air agents are needed. Here, we have used transgenic Caenorhabditis elegans nematode strains carrying stress-responsive fluorescent reporters and evaluated their ability to sense fungal or chemical toxins, especially those that are present in moisture-damaged buildings. Liquid-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Paavanen-Huhtala et al [ 11 ] introduced an easy, comprehensive, and ethically acceptable in vivo model system to monitor the response of multicellular organisms to indoor air toxicity using transgenic Caenorhabditis elegans nematode strains carrying stress-responsive fluorescent reporters. The authors evaluated the nematodes’ ability to sense toxins, especially those that are present in fungi or in moisture-damaged building materials.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Paavanen-Huhtala et al [ 11 ] introduced an easy, comprehensive, and ethically acceptable in vivo model system to monitor the response of multicellular organisms to indoor air toxicity using transgenic Caenorhabditis elegans nematode strains carrying stress-responsive fluorescent reporters. The authors evaluated the nematodes’ ability to sense toxins, especially those that are present in fungi or in moisture-damaged building materials.…”
mentioning
confidence: 99%
“…The contributors to this Special Issue provided insights into current issues in indoor mycology, particularly from a methodological [ 6 , 7 , 8 , 11 , 13 ], metabolic/toxicological [ 10 , 11 , 12 , 14 , 15 ], and taxonomical [ 8 , 9 , 13 , 16 , 17 ] point of view. Overall, two key messages emerge: (i) the current detection methods appear to be shifting from air sampling [ 11 , 12 ] to dust sampling [ 6 , 8 , 9 , 10 , 13 ], as the latter provides information on longer exposure periods and a higher biodiversity; (ii) the microbial composition of buildings is still largely unknown [ 9 , 13 , 16 , 17 ]. Our authors demonstrated that the indoor environment should also be a focus of taxonomical research, especially with regard to wooden and cellulosic materials [ 14 , 15 , 16 , 17 ], which proved to have a relatively high biodiversity.…”
mentioning
confidence: 99%
See 1 more Smart Citation